Diagnóstico de la calidad de energía en la planta de procesamiento de Inversiones el Dorado S.A.S. en la ciudad de Duitama - Ballesteros Gómez, Jorge Luis; Ortiz Jaime, Anderson (Universidad Antonio Nariño, 2024)
The work focuses on diagnosing the quality of energy at the processing plant of Inversiones Eldorado SAS in Duitama. The plant is a company dedicated to the production and distribution of meat products, especially chicken meat, with a prominent history in the Boyacá department.